Cell Death Pathways in Astrocytes with a Modified Model of Oxygen-Glucose Deprivation - Huang, Qiaoying; Zhang, Rui; Zou, Liang yu; Cao, Xu; Chu, Xiaofan (PLOS ONE, 2013)
Traditional oxygen-glucose deprivation (OGD) models do not produce sufficiently stable and continuous deprivation to induce cell death in the ischemic core. Therefore, we modified the OGD model to mimic the observed damage in the ischemic core following stroke and utilized this new model to study cell death pathways in astrocytes. The PO2 and pH levels in the astrocyte culture medium were compared between a physical OGD group, a chemical OGD group and a mixed OGD group. The mixed OGD group was able to maintain anaerobic conditions in astrocyte culture medium for 6 h, while the physical and the chemical groups failed to maintain such conditions. Astrocyte viability decreased and LDH release into in the medium increased as a function of exposure to OGD. Compared to the control group, the expression of active caspase-3 in the mixed OGD group increased within 2 h after OGD, but decreased after 2 h of OGD. Additionally, porimin mRNA levels did not significantly increase during the first 2 h of OGD, while bcl-2 mRNA levels decreased at 1 h. However, both porimin and bcl-2 mRNA levels increased after 2 h of OGD; interestingly, they both suddenly decreased at 4 h of OGD. Taken together, these results indicate that apoptosis and oncosis are the two cell death pathways responsible for astrocyte death in the ischemic core. However, the main death pathway varies depending on the OGD period.